Theophylline as an adjunct to control malignant ventricular arrhythmia associated with early repolarization. Issue 5 (7th December 2017) - Perrin, Tilman; Guieu, Regis; Koutbi, Linda; Franceschi, Frédéric; Hourdain, Jérôme; Brignole, Michele; Deharo, Jean‐Claude
Abstract: Early repolarization (ER) has been associated with an increased risk of sudden cardiac arrest. Interestingly, ventricular arrhythmias seem to be triggered by parasympathetic stimulation. In the present case report, we describe complete control of highly frequent malignant ventricular arrhythmias after adding theophylline to ineffective oral hydroquinidine and high‐rate pacing in a patient suffering from malignant ER. We hypothesize that the theophylline‐mediated enhanced beta‐adrenergic stimulation could reduce the transmural myocardial voltage discrepancy by increasing the inward ICa, L current.